2022
DOI: 10.1186/s10194-022-01384-1
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy profile of noninvasive vagus nerve stimulation on cortical spreading depression susceptibility and the tissue response in a rat model

Abstract: Background Noninvasive vagus nerve stimulation (nVNS) has recently emerged as a promising therapy for migraine. We previously demonstrated that vagus nerve stimulation inhibits cortical spreading depression (CSD), the electrophysiological event underlying migraine aura and triggering headache; however, the optimal nVNS paradigm has not been defined. Methods Various intensities and doses of nVNS were tested to improve efficacy on KCl-evoked CSD freq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 70 publications
2
12
0
Order By: Relevance
“… Li et al (2020) found that the protein and mRNA expression levels of α7nAchR in the peri-infarct cortex examined by Western blotting, quantitative polymerase chain reaction (qPCR), and immunohistochemistry decreased 14 days after MCAO and that taVNS reversed the α7nAchR reduction. In addition, Liu et al (2022) found that a significant decrease in the expression of cortical cyclooxygenase-2, calcitonin gene-related peptide in trigeminal ganglia and c-Fos in trigeminal nucleus caudalis after tcVNS administration, indicating that tcVNS also attenuated the cortical neuroinflammation.…”
Section: The Underlying Mechanism Of Vagus Nerve Stimulation In Strokementioning
confidence: 91%
See 1 more Smart Citation
“… Li et al (2020) found that the protein and mRNA expression levels of α7nAchR in the peri-infarct cortex examined by Western blotting, quantitative polymerase chain reaction (qPCR), and immunohistochemistry decreased 14 days after MCAO and that taVNS reversed the α7nAchR reduction. In addition, Liu et al (2022) found that a significant decrease in the expression of cortical cyclooxygenase-2, calcitonin gene-related peptide in trigeminal ganglia and c-Fos in trigeminal nucleus caudalis after tcVNS administration, indicating that tcVNS also attenuated the cortical neuroinflammation.…”
Section: The Underlying Mechanism Of Vagus Nerve Stimulation In Strokementioning
confidence: 91%
“…In another study, Chen et al (2016) found that both iVNS and tcVNS significantly inhabits CSD susceptibility in the occipital cortex in rats, and this effect occurred within 30 min after vagus nerve stimulation and lasts for more than 3 h. Morais et al (2020) investigated the central and peripheral mechanisms underlying iVNS and tcVNS efficacy on CSD and found that CSD suppression by VNS is mediated by activation of the vagal visceral sensory afferents relaying in nucleus tractus solitarius and in turn projecting to subcortical neuromodulatory centers. To further determine the optimal tcVNS paradigm of CSD suppression, Liu et al (2022) tested the efficacy of various intensities and doses of tcVNS on CSD frequency and electrical threshold of CSD and found that two 2-min nVNS 5 min apart afforded the highest efficacy on electrical CSD threshold and frequency of CSD, suggesting that tcVNS inhabits CSD susceptibility in an intensity-dependent manner. Given the importance of the spreading depolarization mechanism in the physiological and pathological processes of ischemic stroke and the lack of sufficient research evidence to elucidate the specific effects of 10.3389/fnins.2022.1043446 VNS on SDs in rodent models of cerebral ischemia, this field remains to be further explored.…”
Section: Reducing Spreading Depolarizationmentioning
confidence: 99%
“…The VNS paradigm followed the protocol described in our previous studies (1)(2)(3). Briefly, non-invasive VNS was delivered by attaching two disc electrodes (6 mm in diameter) of a hand-held stimulator for rats (a 5 kHz sine wave per millisecond repeating at a rate of 25 Hz; gammaCore; electroCore Medical, LLC, Basking Ridge, NJ, USA) to shaved, intact skin where the cervical vagal nerve was located.…”
Section: Non-invasive Vnsmentioning
confidence: 99%
“…A study by Liu et al [2 ▪ ] examined the inhibitory effects of transcutaneous cervical vagal nerve stimulation on cortical spreading depression in rats. The investigators examined the effects of chronic daily stimulation and episodic stimulation with a custom made gammaCore device and used low intensity, medium intensity and high intensity currents to deliver the stimulation (1 V, 11.4 V, 24.4 V respectively).…”
Section: Evidence From Basic Sciencementioning
confidence: 99%
“…The links between the pathobiology of headache and vagal neuromodulation are still being explored and some probable mechanisms of therapeutic benefit have been proposed. These mechanisms include; modulation of the nucleus of tractus solitarius, locus coeruleus, parabrachial nucleus; descending inhibition, inhibition of Cortical Spreading Depression, modulation of trigeminal nucleus, restoration of impaired sensory feedback and amelioration of autonomic symptoms [1,2 ▪ ]. There are few clinical studies that explore the mechanism of action of VNS in headache medicine.…”
Section: Introductionmentioning
confidence: 99%